ANALISA USAHA PETERNAKAN SAPI RAMBON PADA SKALA USAHA PETERNAKAN RAKYAT DI KECAMATAN GLAGAH KABUPATEN BANYUWANGI - Eko Nugroho (Faculty of Animal Science, Universitas Brawijaya, 2010)
ABSTRACT The research was conducted at Kemiren Village in Glagah District-Banyuwangi Regency. The objective of the research was to analyze the farmer’s income from Rambon cattle farming practices. Sixty-five farmers were selected and interviewed using purposive random sampling method. Descriptive analysis and input-output analysis were applied to the data available. It was found that the average production cost of Rambon cattle farming was Rp. 4.492.425,26 per year while the average revenue was Rp. 6.203.076,93 per year, so that the average cash profit from Rambon cattle farming was Rp.1.699.606,80 per year. It was concluded that Rambon cattle farming was not profitable economically because another non cash expenditure i.e family labor did not take into account. Based on the statements above, the research would recommend that farmers should take another non cash expenditure into consideration when they want to sell their cattle (JIIPB 2010 Vol 20 No1:77-85). Key words: Rambon Cattle Farming, Profitability